Politik Hukum Reformasi Kepolisian Indonesia: Analisis Audiensi KR-Polri dengan Lembaga Pengawas Nasional - Gita Silpiani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The reform of the Indonesian National Police (Polri) has been an ongoing agenda since the 1998 reform era, aiming to build a professional, accountable, and democratic police institution. However, various issues such as low public trust, weak oversight, and the rise in reports of maladministration indicate that the reform has not fully achieved its intended goals. The establishment of the Commission for the Acceleration of National Police Reform (KR-Polri) in 2025, particularly through hearings with national supervisory institutions such as the Indonesian Ombudsman, the National Police Commission, and the Witness and Victim Protection Agency, is a crucial momentum in determining the legal policy direction of police reform. This study aims to analyze the legal policy direction of Indonesian police reform through the KR-Polri hearing process with national supervisory institutions. The research method used is normative legal research with a statutory and conceptual approach, as well as descriptive analysis of legal materials. The results show that the KR-Polri hearings proposed strengthening the authority of the National Police Commission (Kompolnas), increasing accountability, and protecting witnesses and victims within the police system. In conclusion, future police reform requires the creation, revision, and harmonization of legal products to align with the principles of the rule of law, democracy, and human rights protection. Legal reform policies can be directed at a comprehensive revision of Law Number 2 of 2002 concerning the Indonesian National Police, or at least key substantive changes related to oversight mechanisms, transparency of law enforcement, recruitment, and the accountability system for police leaders. These revisions are intended to eliminate provisions that open up room for abuse of authority and impunity, and replace them with regulations that are more in line with the principles of the rule of law and democracy.